Blindness and Visual Impairment in Germany: A Slight Fall in Prevalence - Finger, Robert P (Deutscher Arzte Verlag, 2012)
BACKGROUND: Some 70% of all cases of blindness in Germany are due to diseases of old age. As the population at large is aging, the prevalence of blindness and visual impairment would be expected to rise. To assess this, we studied prevalence trends in Germany over the past three decades. METHODS: We calculated the age- and sex-standardized prevalence of blindness in Germany using data from the archive of the blind registry of the Rhineland Regional Council (Landschaftsverband Rheinland, LVR) for the years 1978 to 2006. We then validated the findings with the aid of data on blindness and visual impairment from the Statistics on Severe Disability (Schwerbehindertenstatistik, SBS) that are published periodically by the German Federal Statistical Office. RESULTS: The number of registered blind persons in the Rhineland increased from 10 665 in 1978 to 12 706 in 1987 and 15 766 in 1997, but it changed little thereafter, remaining at 15 725 in 2006. There was a corresponding trend in the prevalence of blindness in the Rhineland, which rose from 116.8 to 165.6 per 100 000 persons from 1978 to 1997 but was roughly the same, at 163.1 per 100 000 persons, in 2006. The SBS data on blindness and visual impairment reveal a decline in prevalence from 392 to 372 per 100 000 persons between 1987 and 2005. The standardized prevalence rates for blindness and visual impairment in Germany have been declining slowly since about 1997. DISCUSSION: Blindness and visual impairment have become slightly less common in Germany, even though the population is aging. This may be due, at least in part, to better eye health care.